Futebol, memória e identidade operária: uma análise sobre a prática futebolística em Pelotas nas décadas de 1930 a 1960 - Cunha, Aline Nunes da (2008)
The present work intends to analyze soccer as an important sporting practice in the educative formation of two segments of the Pelotense working class in the decades from 1930 to 1960 in Pelotas. Due to the great number of teams which originated from factories, it was decided to do the research on two entities that still maintain soccer as one of the sporting practices which are offered to the residents of Zona do Porto (a neighborhood near the harbor in the city of Pelotas). Esporte Clube Fiação e Tecidos and Sudeste Futebol Clube were the two clubs that were investigated in this study. Through the collected testimonies we realized that soccer transcended the objectives of the industrialists that had the intention of watching the free time of the workers, disciplining bodies and controlling behaviors. In the reports of the workers-players the experience with soccer allowed them to make friends, to share knowledge, as well as it presented itself as a form of social ascending practice and a way of conquering a job, but, principally, it represented an experience that used to cause, and still causes, effects in the constitution of the subjects who practice it.